2022
DOI: 10.31234/osf.io/rtyfm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Narcissists are not more egocentric: evidence from a performance-based perspective-taking measure

Abstract: Narcissists are typically described as egocentric, meaning they behave and think without considering what others might think or feel, which led authors to claim that narcissists’ interpersonal difficulties stem from reduced perspective-taking abilities; a claim supported by self-reported measures of perspective taking. This study examined perspective-taking performance via a visual perspective-taking task along with the Narcissistic Personality Inventory (NPI; Raskin & Terry, 1988) and the Narcisistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
2
1
0
Order By: Relevance
“…In the same vein, a negative correlation was found between the IRI's PT and the VPT's SOP median response time (r(39) = -0.401, p = .011), indicating that participants who scored higher on the PT subscale tended to respond faster when they were required to adopt the other's perspective compared to their own in the VPT task. This result replicates the significant associations previously found in studies conducted on samples of students and narcissistic participants (while controlling for the level of narcissism; Bukowski & Samson, 2017;Bukowski et al, 2022). This finding supports our assumption that both measures reflect one's motivation and sensitivity toward the other.…”
Section: Aspds?supporting
confidence: 90%
See 1 more Smart Citation
“…In the same vein, a negative correlation was found between the IRI's PT and the VPT's SOP median response time (r(39) = -0.401, p = .011), indicating that participants who scored higher on the PT subscale tended to respond faster when they were required to adopt the other's perspective compared to their own in the VPT task. This result replicates the significant associations previously found in studies conducted on samples of students and narcissistic participants (while controlling for the level of narcissism; Bukowski & Samson, 2017;Bukowski et al, 2022). This finding supports our assumption that both measures reflect one's motivation and sensitivity toward the other.…”
Section: Aspds?supporting
confidence: 90%
“…While we reported some important criticisms regarding self-reported evaluation in ASPD, we demonstrated that using a novel index of SOD based on IRI scores was relevant to assess this specific facet, as it showed to be significantly associated with the SOD index obtained with a behavioral task and differentiated the ASPDs from the control group. Further, we replicated the significant correlation between the SOP index and the IRI's PT subscale found in previous studies (Bukowski et al, 2022;Bukowski & Samson, 2017), hence confirming the ability of the VPT task to, first, precisely quantify the attentional priority allocated for selfinformation compared to information about others (SOP), and second, to specifically capture the ability to disentangle information coming from the self and from the others (SOD). Nevertheless, promising work is emerging in this direction (e.g., Krol & Bartz, 2022).…”
Section: Altered Self-other Distinction In Aspd 29supporting
confidence: 85%
“… 3 Egocentricity and selflessness can have various connotations ( Millière, 2020 ). Egocentricity is often contrasted with the capacity for taking on others’ perspectives (e.g., Bukowski et al, 2022 ). The egocentric attributions of salience do not concern solely the capacity for perspective-taking.…”
mentioning
confidence: 99%